Neoadyuvant Hormonotherpy for Posmenopausics Women with Locallity Advanced Breast Cancer (Journal of Analytical Oncology, 2013)
Objective: Present display the objective respond, frequency complete clinical response and pathological complete response with the use of induction hormonotherapy in posmenopausic women with locally advanced breast cancer, (stages III).Methods: Analysis ina Regional General Hospital of a State of Mexico, Mexico;80 patients with chanalicular infiltrate breast cancer. Positive hormonal receptors: estrogen and progesterone, inmunohistochemical study with Her2 and p53. Eligibles patients were treated in a prospective study, to double blind, using per os: letrozol, 2.5 mg; exemestan, 25 mg and anastrozol, 1 mg with aromatase inhibitors; tamoxifen, 20 mg; during 36 consecutive months. Reports were taken at the beginning, subsequent to 3 months and 6 months ago to evaluate the frequency of objective respond. Patients, whom did not show response to neoadjuvant therapy, became treatment with radiotherapy. Patients, whom showed complete or partial clinical respond, went candidates to radical mastectomy. It was used statistical method Chi 2, with p of Mantel-Haenzel table to evaluate differences.Results: During a period of 3 years, january of the 2006 to january of the 2009, 4 groups of patients, 80 studied altogether; the age average was 66.5 years old, with a rank of 45 to 75 years with breast cancer, stages IIIA to IIIB, FIGO stages. Objective respond, OR=55%, 44 patients; Clinical respond, 32 patients (40%); ClR plus CPR, complete pathological respond, 12 patients (15%), p=0.05; Complete pathologicalrespond was founded in 12 patients (15%); 40% with aromatase inhibitors and with tamoxifén TMX, 15%, p=0.05. Without Clinical respond (